Implementation of Circular Economy Model in Textile Industry in Purwakarta: Innovative Strategy Towards Sustainable Production - Ghiffari, M. Amirul; Christian Sondakh, Rian; Pambudi Nurwantara, Ma'ruf (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2025)
This Study Aims to examine the implementation of the circular economy model in textile industry in Purwakarta Regency, West Java. Using a qualitative approach and case studies from some textile companies. The research explores the application of waste reduction (reduce), Reuse and Recycling with production operations. Data were collected through in depth interviews, field observations, and documentation, and analyzed using the miles and Huberman interactive analysis model. The findings indicate that circular economy practices have been partially implemented, particularly in water efficienscy, waste management, and fabric residue processing. However, implementation still faces challenge such as limited technology, low internal awareness, and suboptimal support from local government policies. The study recommends a synergetic collaboration between industry players, government, and academia to foster a sustainable circular economy ecosystem in the textile sector